Employment Outcomes After Critical Illness: An Analysis of the Bringing to Light the Risk Factors and Incidence of Neuropsychological Dysfunction in ICU Survivors Cohort - Norman, Brett C; Jackson, James C; Graves, John A; Girard, Timothy D; Pandharipande, Pratik P; Brummel, Nathan E; Wang, Li; Thompson, Jennifer L; Chandrasekhar, Rameela; Ely, E Wesley (Critical care medicine, 2016)
To characterize survivors' employment status after critical illness and to determine if duration of delirium during hospitalization and residual cognitive function are each independently associated with decreased employment. Prospective cohort investigation with baseline and in-hospital clinical data and follow-up at 3 and 12 months. Medical and surgical ICUs at two tertiary-care hospitals. Previously employed patients from the Bringing to Light the Risk Factors and Incidence of Neuropsychological Dysfunction in ICU Survivors study who survived a critical illness due to respiratory failure or shock were evaluated for global cognition and employment status at 3- and 12-month follow-up. We used multivariable logistic regression to evaluate independent associations between employment at both 3 and 12 months and global cognitive function at the same time point, and delirium during the hospital stay. At 3-month follow-up, 113 of the total survival cohort of 448 (25%) were identified as being employed at study enrollment. Of these, 94 survived to 12-month follow-up. At 3- and 12-month follow-up, 62% and 49% had a decrease in employment, 57% and 49% of whom, respectively, were newly unemployed. After adjustment for physical health status, depressive symptoms, marital status, level of education, and severity of illness, we did not find significant predictors of employment status at 3 months, but better cognition at 12 months was marginally associated with lower odds of employment reduction at 12 months (odds ratio, 0.49; p = 0.07). Reduction in employment after critical illness was present in the majority of our ICU survivors, approximately half of which was new unemployment. Cognitive function at 12 months was a predictor of subsequent employment status. Further research is needed into the potential relationship between the impact of critical illness on cognitive function and employment status.